1989
DOI: 10.1111/j.1365-3083.1989.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV in Human T Lymphocytes

Abstract: Specific inhibitors of the membrane-bound dipeptidyl peptidase IV (DP IV) and polyclonal antibodies against this enzyme were used to investigate the relationships between DP IV activity and the production and action of T cell-derived lymphokines. Production of interleukin 2 (IL-2) and gamma interferon by mitogen plus phorbol ester-stimulated mononuclear cells from human blood was found to be reduced in the presence of N-Ala-Pro-O-(nitrobenzoyl-)-hydroxylamine, epsilon-(4'-nitro) benzoxycarbonyl-Lys-Pro, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…A similar specific inhibition of antigen-induced IL-2 production was also observed in D1.1 cell cultures (data not shown). These results were somewhat unexpected in light of the previous reports by Schon and coworkers (21)(22)(23)) that DP-IV inhibitors suppress both antigen-and mitogen-induced T-cell proliferation and IL-2 production. The reasons for this discrepancy are not clear at present.…”
Section: Methodscontrasting
confidence: 51%
See 1 more Smart Citation
“…A similar specific inhibition of antigen-induced IL-2 production was also observed in D1.1 cell cultures (data not shown). These results were somewhat unexpected in light of the previous reports by Schon and coworkers (21)(22)(23)) that DP-IV inhibitors suppress both antigen-and mitogen-induced T-cell proliferation and IL-2 production. The reasons for this discrepancy are not clear at present.…”
Section: Methodscontrasting
confidence: 51%
“…This proposal is based on experiments in which the addition of DP-IV inhibitors and DP-IV antibodies to cell culture systems suppressed mitogenand alloantigen-induced T-cell proliferation, IL-2 production (22), and impaired T-cell-directed B-cell differentiation and immunoglobulin production (23,24). Circumstantial support for this proposal comes from the observation that a number of cytokines have DP-IV susceptible Ala-Pro N-terminal sequences, as this suggests a plausible mechanism for the proposed involvement of DP-IV in T-cell activation events.…”
mentioning
confidence: 99%
“…DPPIV enzyme activity has been implicated in antigeninduced and/or mitogen-induced T-cell proliferation and lymphokine production, by studies done with enzyme inhibitors (25)(26)(27). These studies principally suggested that DPPIV activity is necessary for certain T-cell activation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…cytokine production, B cell differentiation, and immunoglobulin secretion [12][13][14][15][16][17]. However, the function of DP IV in the proliferation and differentiation processes has not been resolved yet.…”
Section: Introductionmentioning
confidence: 99%